Global Research Trends of Role-play Method in English Language Teaching: A Bibliometric Analysis - Saleh, Yuwin Rustam; Ismail, Abdul Kadir; Ayuba, Hasan; Ladja, Witan (English Education Department at FKIP Nommensen University, 2025)
This study examines global research trends, thematic development, and prospective directions of the role-play method in English Language Teaching (ELT) from 2000 to 2025 via an extensive bibliometric analysis. 81 Scopus-indexed publications were methodically chosen based on established inclusion and exclusion criteria. The analysis, conducted using VOSviewer and Bibliometrics (Biblioshiny), indicated substantial post-pandemic growth in publications, propelled by incorporating digital assessment, task-based learning, and online communicative methodologies. The results indicate a thematic shift in role-play from an auxiliary technique to a fundamental educational strategy associated with 21st-century skills. Furthermore, international collaboration networks and theme clusters underscore the method’s versatility across educational and cultural settings. This study presents theoretical, methodological, and practical contributions, offering significant insights for researchers, educators, and policymakers in the dynamic English Language Teaching (ELT) field.